1991
DOI: 10.1007/bf01244702
|View full text |Cite
|
Sign up to set email alerts
|

Role of presynaptic serotonergic receptors on the mechanism of action of 5-HT1A and 5-HT1B agonists on masculine sexual behaviour: physiological and pharmacological implications

Abstract: In order to establish whether the 5-HT1A or the 5HT1B agonists, 8-OH-DPAT or TFMPP, produce their facilitatory or inhibitory actions on masculine sexual behaviour via a mechanism involving: (a) the serotonin synthesis or release; (b) the stimulation of presynaptic receptors, or (c) the stimulation of somatodendritic receptors, three series of experiments were performed. The administration of the serotonin synthesis inhibitor, p-chlorophenylalanine (p-CPA, 300 mg/kg x 3 days), facilitated sexual behaviour but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Conversely, drugs that reduce 5-HT neurotransmission by antagonizing postsynaptic 5-HT receptors or acting as agonists at 5-HT 1A autoreceptors facilitate sex behavior (Ahlenius, Larsson, & Arvidsson, 1989;Da Prada, Bonetti, Scherschlicht, & Bondiolotti, 1985;Fernandez-Guasti & Escalante, 1991). Furthermore, the administration of 5,7-dihydroxytryptamine or p-chloroamphetamine (drugs that selectively destroy 5-HT nerve terminals) also stimulates sexual behavior (Da Prada, Pieri, Keller, Pieri, & Bonetti, 1978;Fernandez-Guasti & Escalante, 1991;Sodersten, Berge, & Hole, 1978). However, it has been noted that an extensive lesion is necessary to achieve this behavioral effect (Sodersten et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, drugs that reduce 5-HT neurotransmission by antagonizing postsynaptic 5-HT receptors or acting as agonists at 5-HT 1A autoreceptors facilitate sex behavior (Ahlenius, Larsson, & Arvidsson, 1989;Da Prada, Bonetti, Scherschlicht, & Bondiolotti, 1985;Fernandez-Guasti & Escalante, 1991). Furthermore, the administration of 5,7-dihydroxytryptamine or p-chloroamphetamine (drugs that selectively destroy 5-HT nerve terminals) also stimulates sexual behavior (Da Prada, Pieri, Keller, Pieri, & Bonetti, 1978;Fernandez-Guasti & Escalante, 1991;Sodersten, Berge, & Hole, 1978). However, it has been noted that an extensive lesion is necessary to achieve this behavioral effect (Sodersten et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that treatment of rats with drug regimens that result in increased 5-HT neurotransmission-including drugs that evoke 5-HT release, stimulate 5-HT synthesis, or inhibit 5-HT reuptake-results in a decrease in male copulatory behavior (Ahlenius & Larsson, 1991;Ahlenius, Larsson, & Svensson, 1980;Foreman, Hall, & Love, 1992). Conversely, drugs that reduce 5-HT neurotransmission by antagonizing postsynaptic 5-HT receptors or acting as agonists at 5-HT 1A autoreceptors facilitate sex behavior (Ahlenius, Larsson, & Arvidsson, 1989;Da Prada, Bonetti, Scherschlicht, & Bondiolotti, 1985;Fernandez-Guasti & Escalante, 1991). Furthermore, the administration of 5,7-dihydroxytryptamine or p-chloroamphetamine (drugs that selectively destroy 5-HT nerve terminals) also stimulates sexual behavior (Da Prada, Pieri, Keller, Pieri, & Bonetti, 1978;Fernandez-Guasti & Escalante, 1991;Sodersten, Berge, & Hole, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…However, neurotoxic lesion of 5-HT cell bodies by i.c.v. or intraraphe microinjection of 5,7-dihydroxytryptamine failed to block the facilitator effects on ejaculation of 8-OH-DPAT systemically delivered (Fernandez-Guasti and Escalante, 1991). This probably rules out the participation of cerebral 5-HT1A autoreceptors to the facilitator effect of 8-OH-DPAT on ejaculation.…”
mentioning
confidence: 92%
“…Among them, the postsynaptic 5-HT 1B and 5-HT 2C receptors have been shown to inhibit ejaculation upon activation (Ahlenius and Larsson 1998;Fernandez-Guasti and Rodriguez-Manzo 1992;Foreman et al 1989;Hillegaart and Ahlenius 1998;Klint et al 1992;Watson and Gorzalka 1991), whereas activation of 5-HT 1A receptors has been shown to accelerate ejaculation (Ahlenius et al 1981;Coolen et al 1997;Fernandez-Guasti and Escalante 1991;Haensel and Slob 1997;Rehman et al 1999). …”
Section: Introductionmentioning
confidence: 97%